2008
DOI: 10.1007/s10409-007-0131-0
|View full text |Cite
|
Sign up to set email alerts
|

Coarse grained molecular dynamics and theoretical studies of carbon nanotubes entering cell membrane

Abstract: Motivated by recent experimental observations that carbon nanotubes (CNT) can enter animal cells, here we conduct coarse grained molecular dynamics and theoretical studies of the intrinsic interaction mechanisms between CNT's and lipid bilayer. The results indicate that CNT-cell interaction is dominated by van der Waals and hydrophobic forces, and that CNT's with sufficiently small radii can directly pierce through cell membrane while larger tubes tend to enter cell via a wrapping mechanism. Theoretical models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 33 publications
1
66
0
Order By: Relevance
“…They also demonstrated that the initial orientation of the NP toward the lipid bilayer strongly relates to the capability of the NP direct permeation across the lipid bilayer. Shi et al (2008) investigated permeation behavior of carbon nanotubes (CNTs) with different tube diameters. Their simulation result showed the tube diameter can be a determinant of the permeation mode of the CNTs: a CNT with smaller tube diameter (single-walled CNT) can directly permeate the bilayer via a piercing mode, while a CNT with larger tube diameter (multi-walled CNT) is likely to translocate the lipid bilayer via a wrapping mode.…”
Section: Biased MD Simulation Studiesmentioning
confidence: 99%
“…They also demonstrated that the initial orientation of the NP toward the lipid bilayer strongly relates to the capability of the NP direct permeation across the lipid bilayer. Shi et al (2008) investigated permeation behavior of carbon nanotubes (CNTs) with different tube diameters. Their simulation result showed the tube diameter can be a determinant of the permeation mode of the CNTs: a CNT with smaller tube diameter (single-walled CNT) can directly permeate the bilayer via a piercing mode, while a CNT with larger tube diameter (multi-walled CNT) is likely to translocate the lipid bilayer via a wrapping mode.…”
Section: Biased MD Simulation Studiesmentioning
confidence: 99%
“…Previous studies of carbon nanotubes entering the cell membrane have suggested that there exists a critical structural dimension on the order of the bilayer thickness (around 4 nm), below which direct penetration into the bilayer becomes possible and above which receptor-mediated endocytosis is needed for the uptake (27)(28)(29). Graphene is atomically thin in one dimension, but typically large in two other dimensions, and our preliminary modeling work showed large energy barriers for membrane penetration even when monolayer sheets encounter the lipid bilayer edge-first.…”
mentioning
confidence: 99%
“…A recent advance in nanoscale technology is the synthesizing of nanotubes with chemical modified surface [4], which allows one to construct functionalized nanotubes that mimic the behavior of biological ion channels and are stable when inserted in a lipid bilayer [5,6], and also exhibit a high-energy barrier [7]. An excellent review of recent theoretical advances in synthetic nanotubes which mimic the behavior of biological ion channels is given by Hilder et al [8].…”
Section: Introductionmentioning
confidence: 99%